Pamidronate Treatment in Charcot Neuro-Osteoarthropathy: Change in Biochemical Markers of Bone Turnover and Radiographic Outcome After Treatment - Vázquez, Ivonne; Moreno, Mireia; Larrosa, Marta (IntechOpen, 2012)
None